An analytical study on conic volume technique vs bounding box technique in picking object in Non Immersive Virtual world (International Journal of Engineering and Computer Science, 2013)
In this paper we present an analytical study to select 3D objects based on their shape pointing device in a virtual environment (VE). We adapt a 2D picking metaphor to 3D selection in Virtual environment’s by changing the projection and view matrices according to the position and orientation of a pointing device and rendering a conic selection volume to an off-screen pixel buffer. This method works for triangulated as well as volume rendered objects, no explicit geometric representation is required. In this paper I focused the advantages of conic volume technique over bounding box technique in picking object in Non immersive Virtual world. The usefulness and effectiveness of the proposed evaluation measures are shown by reporting the performance evaluation of two algorithms. We then compare the application of both techniques with related work to demonstrate that they are more suitable